BENTUK DAN MAKNA PENAMAAN JENIS-JENIS PADI DALAM BAHASA BOKIDOH DAYAK JANGKANG - Fasifikus Rafael Een; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe formulation of the problem in this study includes the form of words or phrases, lexical meanings, how to name rice in the Bokidoh Dayak Jangkang language, and the making of descriptive texts as teaching materials for seventh grade junior high school students. This study used descriptive qualitative method. Sources of data from native speakers are active rice farmers. The data obtained are in the form of words or phrases for the name of rice, the lexical meaning of rice varieties, and the method of naming each type of rice. Data collection techniques are interviews, recording, and recording. The data obtained are 41 types of rice, word forms totaling 33 total data in the form of monofermic nouns, phrase forms totaling 8 data for noun categories, lexical meaning based on phenotype. There are 6 ways of naming, namely 5 data for mentioning characteristics, 2 data based on the inventor and maker, 12 data for mentioning the place of origin, 15 data for similarity, 3 data for new plantings, and 4 data for definition. This research is associated with learning Indonesian in class VII SMP in semester 1 of the 2013 Curriculum as teacher enrichment material.Keyword: Bokidoh Language, Naming, Type of Rice